2020
DOI: 10.3390/molecules25214923
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile and Use of the Peat as an Adsorbent for Extraction of Volatile Compounds from Leaves of Geranium (Pelargonium graveolens L’ Herit)

Abstract: Volatile organic compounds (VOCs) from leaves of geranium (Pelargonium graveolens L’ Herit) were extracted by dynamic headspace using Porapak Q (HSD-P) as adsorbent and peat, a novel adsorbent in the extraction of plant volatiles, analyzed by gas chromatography–mass spectrometry (GC/MS) and gas chromatography–flame ionization (GC/FID), and the results were compared with those obtained by hydrodistillation (HD). The yield volatiles changed with the extraction method. HD was more efficient for extracting linaloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the recovery of volatile terpenoids, differences have been observed in the type of compounds that are obtained when using steam distillation methods and those of adsorption. In the study carried out by Niculau et al (2020) on the extraction of volatile terpenoids from geranium, it was shown that there are differences in the profile of compounds recovered with hydrodistillation and two dynamic adsorption methods for the headspace. With hydrodistillation, no monoterpenes were recovered, only monoterpenoids, sesquiterpenes, and esters, of which the main ones are linalool and citronellyl formate, in a higher proportion compared to adsorption methods.…”
Section: Recovery Of Terpenes and Terpenoids With Steam Distillation ...mentioning
confidence: 99%
“…In the recovery of volatile terpenoids, differences have been observed in the type of compounds that are obtained when using steam distillation methods and those of adsorption. In the study carried out by Niculau et al (2020) on the extraction of volatile terpenoids from geranium, it was shown that there are differences in the profile of compounds recovered with hydrodistillation and two dynamic adsorption methods for the headspace. With hydrodistillation, no monoterpenes were recovered, only monoterpenoids, sesquiterpenes, and esters, of which the main ones are linalool and citronellyl formate, in a higher proportion compared to adsorption methods.…”
Section: Recovery Of Terpenes and Terpenoids With Steam Distillation ...mentioning
confidence: 99%
“…is an aromatic herb in the Geraniaceae family that is native to a few geographical areas of South Africa, and mainly distributed throughout the Mediterranean region [ 14 , 15 ]. Around the world, PGEO is widely utilized as a pharmaceutical, cosmetic, and flavoring agent as well as in folkloric foods and aromatherapy industries [ 14 , 16 , 17 ]. It is one of the best oils utilized in skincare due to its effectiveness in cleaning oily skin and opening pores.…”
Section: Introductionmentioning
confidence: 99%